A CRISPR-Cas-based recombinase polymerase amplification assay for ultra-sensitive detection of active Trypanosoma brucei evansi infections - Álvarez-Rodríguez, Andrés; Li, Zeng; Jin, Bo-Kyung; Stijlemans, Benoit; Geldhof, Peter; Magez, Stefan (Frontiers in Molecular Biosciences, 2025)
IntroductionControl of Trypanosoma brucei evansi (T. b. evansi) infections remains a significant challenge in managing Surra, a widespread veterinary disease affecting both wild and domestic animals. In the absence of an effective vaccine, accurate diagnosis followed by treatment is crucial for successful disease management. However, existing diagnostic methods often fail to detect active infections, particularly in field conditions. Recent advancements in CRISPR-Cas technology, combined with state-of-the-art isothermal amplification assays, offer a promising solution. This approach has led us to the development of a TevRPA-CRISPR assay, a highly sensitive and specific T. b. evansi diagnostic tool suitable for both laboratory and field settings.MethodsFirst, the TevCRISPR-Cas12b cleavage assay was developed and optimized, and its analytical sensitivity was evaluated. Next, this technology was integrated with the TevRPA to create the TevRPA-CRISPR test, with the reaction conditions being optimized and its analytical sensitivity and specificity assessed. Finally, the test’s accuracy in detecting both active and cured T. b. evansi infections was evaluated.ResultsThe optimized TevCRISPR-Cas12b cleavage assay demonstrated the ability to detect T. b. evansi target DNA at picomolar concentrations. Integrating TevCRISPR-Cas12b with RPA in Two-Pot and One-Pot TevRPA-CRISPR tests achieved up to a 100-fold increase in analytical sensitivity over RPA alone, detecting attomolar concentrations of T. b. evansi target DNA, while maintaining analytical specificity for T. b. evansi. Both assays exhibited performance comparable to the gold standard TevPCR in experimental mouse infections, validating their effectiveness for detecting active infections and assessing treatment efficacy.DiscussionThe TevRPA-CRISPR tests prove highly effective for diagnosing active infections and assessing treatment efficacy, while being adaptable for both laboratory and field use. Thus, the TevRPA-CRISPR assays emerge as a promising addition to current diagnostic tools, offering efficient and reliable detection of active T. b. evansi infections.